Static and dynamic abductor function are both associated with physical function 1 to 5 years after total hip arthroplasty. (July 2019) - Cinnamon, Christopher C.; Longworth, Jessica A.; Brunner, J. Heather; Chau, Vivian K.; Ryan, Colleen A.; Dapiton, Kris R.; Chmell, Samuel J.; Foucher, Kharma C.
Abstract: Background: A subset of total hip arthroplasty patients experience functional impairments past the first postoperative year. Poor hip abductor function is common before and in the early postoperative period. It is not known if abductor impairment is associated with long-term functional impairment. This study evaluated the relationships between static and dynamic abductor function and performance-based and self-reported function >1 year post-total hip arthroplasty. Methods: Eighteen adults 1–5 years post-total hip arthroplasty participated. Static and dynamic abductor function were assessed through dynamometry and gait analysis, respectively. Subjects completed four physical performance tests and two self-report instruments. Findings: Higher peak isometric abductor strength was associated with better performance-based function ( P  ≤ 0.001–0.030) and with self-reported function ( P  ≤ 0.001–0.012). Higher peak external adduction moment was associated with better results on 3 of 4 performance tests ( P  = 0.007–0.026). Together, static and dynamic abductor function predicted 35–77% of the variation in physical function. Abductor strength best predicted walking test results and self-reported function, while dynamic abductor function best predicted tests involving sit-to-stand Interpretation: Static and dynamic abductor function were associated with physical function 1–5 years after total hip arthroplasty. These results support further investigation of interventions targeting abductor function for persons experiencing persistent impairments. Highlights: Hip abductor strength is associated with performance tests after total hip arthroplasty. Hip abductor strength is associated with self-reported function after total hip arthroplasty. Peak external adduction moments are associated with most performance tests. Peak external adduction moments are not associated with self-reported function.